TIPE KEPRIBADIAN TOKOH UTAMA PADA NOVEL “INTROVER” KARYA M.F. HAZIM - Asngadi Rofiq; Muhammad Afifuddin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The author tries to analyze the personality of the main characters using the study of literary psychology, whether the main character is more melancholic or pblegmatic. M.F. Hazim in his novel